1992
DOI: 10.1159/000126089
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Promotes Rapid Desensitization of α<sub>1</sub>-Adrenergic Receptor Augmentation of cAMP Formation in Rat Hypothalamic Slices

Abstract: We previously demonstrated that norepinephrine (NE) induction of cAMP accumulation in slices of the preoptic area (POA) and middle hypothalamus (MH) is reduced by in vivo administration of progesterone to estradiol-primed rats, apparently by eliminating α1-receptor augmentation of β-receptor-stimulated cAMP formation. The present studies examined whether in vitro exposure to progesterone would also depress NE-stimulated cAMP synthesis. POA and MH slices from estradiol-primed females were incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In contrast, preincubation of rat hypothalamic slices with progesterone (20 nM) for 5 min significantly suppressed norepinephrine-stimulated cAMP formation by Ͼ60%. This effect was estrogen dependent in that progesterone in vitro did not inhibit NE-stimulated cAMP accumulation in slices from ovariectomized rats not pretreated with estradiol (371). In addition, progesterone was found to decrease cAMP levels in quiescent adipocytes or in adipocytes stimulated by isoproterenol (470).…”
Section: B Progesteronementioning
confidence: 91%
“…In contrast, preincubation of rat hypothalamic slices with progesterone (20 nM) for 5 min significantly suppressed norepinephrine-stimulated cAMP formation by Ͼ60%. This effect was estrogen dependent in that progesterone in vitro did not inhibit NE-stimulated cAMP accumulation in slices from ovariectomized rats not pretreated with estradiol (371). In addition, progesterone was found to decrease cAMP levels in quiescent adipocytes or in adipocytes stimulated by isoproterenol (470).…”
Section: B Progesteronementioning
confidence: 91%
“…Progesterone may activate membrane receptors coupled to G-proteins [Majewska, 1992;Petitti and Etgen, 1992;Valera et al, 1992;Grazzini et al, 1998]. Progesterone mobilizes calcium from the endoplasmic reticulum and increases the formation of inositol trisphosphate and diacylglycerol via a G-protein insensitive to pertussis toxin in osteoblasts, the bone forming cells, as well as in ovarian granulosa cells .…”
mentioning
confidence: 99%
“…Although numerous studies have suggested that P may affect neurotransmission through a nonnuclear action [25,38,39], little is known about the precise molecular mechanisms underlying such interactions. P can interca late into the lipid bilayer of the cell membrane [40], Thus, the modified lipid environment might be the cause of changes in the three-dimensional structure of 5-HTia receptors resulting in a change in the coupling mecha nisms between the receptor and its agonist or between the receptor and G proteins.…”
Section: Effect O F 8-oh-dpat On Lhrh Release From Fetal Hypothalamicmentioning
confidence: 99%